2021
DOI: 10.3390/nano11123237
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Near-Infrared-Activated Photocatalytic Hydrogen Evolution from Ammonia Borane with Core-Shell Upconversion-Semiconductor Hybrid Nanostructures

Abstract: In this work, the photocatalytic hydrogen evolution from ammonia borane under near-infrared laser irradiation at ambient temperature was demonstrated by using the novel core-shell upconversion-semiconductor hybrid nanostructures (NaGdF4:Yb3+/Er3+@NaGdF4@Cu2O). The particles were successfully synthesized in a final concentration of 10 mg/mL. The particles were characterized via high resolution transmission electron microscopy (HRTEM), photoluminescence, energy dispersive X-ray analysis (EDAX), and powder X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…The H 2 generation activity of Er/Yb-doped TiO 2 was observed to be boosted (10.05 μmol h −1 ) by plasmonic MoO 3−x . Recently, Jing et al 38 have reported a novel core−shell approach to synthesizing a nanostructure comprising NaGd-F 4 :Yb 3+ /Er 3+ @NaGdF 4 @Cu 2 O. The same was examined for its ability to photocatalytically convert ammonia borane (AB) to H 2 (33 μmol h −1 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The H 2 generation activity of Er/Yb-doped TiO 2 was observed to be boosted (10.05 μmol h −1 ) by plasmonic MoO 3−x . Recently, Jing et al 38 have reported a novel core−shell approach to synthesizing a nanostructure comprising NaGd-F 4 :Yb 3+ /Er 3+ @NaGdF 4 @Cu 2 O. The same was examined for its ability to photocatalytically convert ammonia borane (AB) to H 2 (33 μmol h −1 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, hydrogen could play a key role in the future of energy devices and their related implications for economy [ 4 , 5 , 6 , 7 ]. Hydrogen is the most abundant light element of the universe.…”
Section: Introductionmentioning
confidence: 99%